2018
DOI: 10.1200/po.17.00316
|View full text |Cite
|
Sign up to set email alerts
|

Rucaparib Monotherapy in Patients With Pancreatic Cancer and a Known Deleterious BRCA Mutation

Abstract: Purpose Pancreatic cancer has a poor prognosis and limited treatment options. Approximately 9% of pancreatic cancers harbor a germline or somatic BRCA1 or BRCA2 (BRCA1/2) mutation. Because poly (ADP-ribose) polymerase inhibitors have significant activity in BRCA1/2-mutant ovarian and breast cancers, RUCAPANC investigated the efficacy and safety of rucaparib in BRCA1/2-mutant pancreatic cancer. Patients and Methods RUCAPANC enrolled patients with measurable locally advanced/metastatic pancreatic cancer who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(140 citation statements)
references
References 28 publications
(22 reference statements)
4
127
0
1
Order By: Relevance
“…RUCAPANC trial reported 32% ORR among patients with APC harboring BRCA1/BRCA2 mutation. 57 Veliparib on the other hand has not shown any benefit among this patient population. 58,59 Phase III POLO trial 60 APC patients with germline BRCA1/ BRCA2 mutated APC were treated with olaparib 300 mg twice daily or placebo after ≥16 weeks of platinum-based regimen.…”
Section: Pancreatic Cancermentioning
confidence: 76%
“…RUCAPANC trial reported 32% ORR among patients with APC harboring BRCA1/BRCA2 mutation. 57 Veliparib on the other hand has not shown any benefit among this patient population. 58,59 Phase III POLO trial 60 APC patients with germline BRCA1/ BRCA2 mutated APC were treated with olaparib 300 mg twice daily or placebo after ≥16 weeks of platinum-based regimen.…”
Section: Pancreatic Cancermentioning
confidence: 76%
“…Our results support broader panel testing as a way to identify unexpected high-penetrant PVs in eoRC patients, when there is a personal or family history of additional cancers (especially an HBOCsyndrome cancer). This is important because identification of a BRCA PV can potentially change medical management; for instance, PARP inhibitor therapy is effective in tumors with BRCA PVs, including non-breast tumors (24,25). Also, screening and prevention of HBOCsyndrome cancers will be increased significantly in the proband and family members found to have the same PV.…”
Section: Discussionmentioning
confidence: 99%
“…Olaparib is an oral PARP inhibitor that, in the setting of BRCA‐ deficient cells, functions as a cytotoxic agent by blocking base excision repair, which eventually leads to double‐strand breaks, subsequent DNA replication fork stalling, and cell death . In certain cancer types with high mutation rates in genes involved with homologous recombination components, such as high‐grade serous ovarian, triple‐negative breast, metastatic prostate, or pancreatic tumors, PARP inhibitors have proven to be effective treatment strategies .…”
Section: Potential Strategies To Target the Pathway And Implications mentioning
confidence: 99%
“…Olaparib is an oral PARP inhibitor that, in the setting of BRCAdeficient cells, functions as a cytotoxic agent by blocking base excision repair, which eventually leads to double-strand breaks, subsequent DNA replication fork stalling, and cell death [14]. In certain cancer types with high mutation rates in genes involved with homologous recombination components, such as highgrade serous ovarian, triple-negative breast, metastatic prostate, or pancreatic tumors, PARP inhibitors have proven to be effective treatment strategies [15][16][17][18]. Emerging evidence suggests that PARP inhibitors may also be a novel therapeutic option for patients with GBM, given the upregulation of DNA repair genes like ATM, ATR, CHK1, and PARP as well as the high capacity for DNA repair in glioma stem cells [19].…”
Section: Potential Strategies To Target the Pathway And Implications mentioning
confidence: 99%